Effects of Handover Education Using the Outcome-Present State Test (OPT) Model and SBAR in Nursing Students: A Quasi-Experimental Design - Seo, Yon Hee; Jang, Kyeongmin; Ahn, Jung-Won (Iranian journal of public health, 2023)
Background: Since most of nursing students lack clinical reasoning competency, for effective handover education, it is necessary to include a strategy to improve the clinical reasoning competency in the practical training course of the nursing department. Methods: This study used a quasi-experimental research design using a non-equivalent control group pretest-posttest design to verify the effectiveness of the practice education program using the OPT model and SBAR. The subjects were 73 third-year students participating in clinical practice or clinical alternative practice in Korea. Results: The experimental group showed significantly better communication clarity (t=-12.262, P<.001), communication confidence (t=-12.486, P<.001), problem-solving processes (t=-13.100, P<.001), and team efficacy (t=-6.197, P<.001) compared to before the intervention. However, there was no significant difference between the pre- and post-intervention scores of the control group. Conclusion: In a situation where clinical practice is difficult for nursing students, the handover education program using the OPT model and SBAR can helps improve their communication clarity, communication confidence, problem- solving process, and team efficacy.